Asbestos Lobby, TUC Congress, 1976 (1976)
1976 1960-2000 "Asbestos Lobby, TUC Congress, 1976" [T0437.jpg], 1976 The 1976 Congress at Brighton discussed how to make the 1974 Health and Safety at Work act more effective. Outside the Congress Hall, there was a Lobby by 1000 workers from the Isle of grain Power Station who had been sacked by Babcock and Wilcox for refusing to work with asbestos without protective clothing. Following a factory inspection and with the support of the Health and Safety Executive (HSE) the dispute ended after 6 months.